Hubungan Antara Beban Kerja Fisik Dengan Kelelahan Kerja Pada Tenaga Kerja Bagian Produksi Tulangan Beton di PT Wijaya Karya Beton Tbk PPB Majalengka - Nugraheni, Annies Banita; , dr. Hardjanto, M.S., Sp.OK; , Sri Darnoto S.KM M.PH (2015)
The workload is one of the factors that may affect workers experiencing job burnout. Workers who have jobs that are too heavy and excessive muscle contraction will accelerate the body which will accelerate the occurrence of fatigue. Physical workload is excessive and uncontrolled can increase work exhaustion, as well as the level of fatigue on the production of concrete reinforcement that has a significant workload than any other production site. The purpose of this study was to determine the relationship of physical workload with fatigue on the part of workers in the production of concrete reinforcingbPT Wijaya Karya Beton Tbk PPB Majalengka. The research method used observational analytic research with cross sectional approach. The sampling technique using purposive sampling, the sample was 30 workers. Analysis of data used statistical test of Spearman-Rho correlation with a significant level (α = 0.05). Statistical tests using the Spearman-Rho found any significant relationship between physical workload with fatigue (p = 0.000) (r = 0.714) with the level of the relationship strong and indicate the direction of positive correlation. From the results study concluded there is the correlation between work load and fatigue.